Molecular basis of dimer formation during the biosynthesis of benzofluorene-containing atypical angucyclines - Chunshuai Huang (Nature Portfolio, 2018)
Benzofluorene-containing angucyclines, bacterial natural compounds with potential use as therapeutics/antibiotics, occur as dimers. Here, the authors elucidated the dimerization mechanism which turned out to work spontaneously, without enzymatic catalysis.